KOMUNITAS POSITIVE PARENTING “POPSTAR” UNTUK MENINGKATKAN KUALITAS PENGASUHAN - Mauna; Ernita Zakiah; Zarina Akbar (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract The Covid-19 pandemic has resulted in many changes, including more time for parents to interact with their children. The increasing duration of togetherness among family members should be able to improve the quality of interaction between family members. In fact, there is an increasing problem stemming from disharmony in the relationship between children and parents. One of the causes of this problem is the unpreparedness of family members to face changes and the lack of information for parents about positive parenting. The existence of a positive parenting community "POPSTAR" is expected to be a forum for parents to share related problems, providing mutual support between parents who face similar problems. In addition, this community also disseminated material on child development, techniques in positive parenting. Community members are asked to apply the material provided and write it down in a worksheet so that members can experience firsthand the benefits of applying positive parenting. Members who encounter problems when applying positive parenting can ask psychologists in the community Abstrak Pandemik Covid-19 mengakibatkan banyak perubahan diantaranya adalah lebih banyak waktu orangtua untuk berinteraksi dengan anak-anak. Meningkatnya durasi kebersamaan diantara anggota keluarga seharusnya dapat meningkatkan kualitas interaksi antar anggota keluarga. Pada kenyataannya terjadi peningkatan masalah yang bersumber dari ketidakharmonisan hubungan anak dan orangtua. Masalah ini salah satunya disebabkan oleh ketidaksiapan anggota keluarga menghadapi perubahan serta kurangnya informasi yang dimiliki orangtua mengenai pengasuhan positif. Adanya komunitas positive parenting “POPSTAR” diharapkan dapat menjadi wadah berbagi orangtua terkait masalah yang dihadapi, saling memberi dukungan antar orangtua yang menghadapi masalah yang serupa. Selain itu dalam komunitas ini juga disosialisasikan materi mengenai perkembangan anak, teknik-teknik dalam pengasuhan positif. Anggota komunitas diminta menerapkan materi yang diberikan dan menuliskannya dalam lembar kerja sehingga anggota dapat merasakan secara langsung manfaat dari pengaplikasian positive parenting. Anggota yang menemui kendala ketika mengaplikasikan positive parenting dapt bertanya kepada psikolog yang berada di komunitas.